Christianity A short global history - Norris, Frederick W. (Oxford A Oneworld Book, 2002)
A sweeping history of Christianity spans the globe to offer a balanced account of this religion's growth from a radical Jewish sect to a worldwide philosophy with billions of adherents.
Keywords: Christianity - Introduction